2018
DOI: 10.1016/j.ihj.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of premature ventricular complexes induced cardiomyopathy. Influence of concomitant structural heart disease

Abstract: PVCs elimination by RF ablation results in significant improvement even restoration of LV function regardless of PVC origin, or the presence of concomitant SHD. PVCs burden before and after ablation are the main predictors of LVEF recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…With regards to the relationship between PVC origin site and EF recovery, a prior study showed a higher incidence of EF recovery of PVC CM in LV ablations compared to RV ablations, though this was not a statistically significant finding 28 . Our study corroborates this with a significant correlation between RV site and lack of EF recovery.…”
Section: Discussionmentioning
confidence: 86%
“…With regards to the relationship between PVC origin site and EF recovery, a prior study showed a higher incidence of EF recovery of PVC CM in LV ablations compared to RV ablations, though this was not a statistically significant finding 28 . Our study corroborates this with a significant correlation between RV site and lack of EF recovery.…”
Section: Discussionmentioning
confidence: 86%
“…Study characteristics: The electronic search yielded 201 studies. Of the 201, only 11 studies that met the inclusion criteria formed the final dataset for analysis [19][20][21]45,48,[56][57][58][59][60][61]. These studies are relatively recent, published between 2005 [21] and 2018 [61].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 201, only 11 studies that met the inclusion criteria formed the final dataset for analysis [19][20][21]45,48,[56][57][58][59][60][61]. These studies are relatively recent, published between 2005 [21] and 2018 [61]. Except one prospective study [58], the remaining 10 studies adopted a retrospective design [19][20][21]45,48,56,57,[59][60][61].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations